Linguagem e psicanálise: as marcas do sujeito do insconsciente em narrativas escolares - Lima, Magda Wacemberg Pereira (2015)
This present dissertation was motivated by the search for understanding how adolescents, 9th graders of elementary school in a public school of Serra Talhada/PE, when asked to produce narrative texts, with the classic children's tales as a reference, related scenes and characters of the original texts to people and events of their experiences. This phenomenon led us to suppose that the re-writing of scenes and characters roles in students texts could result from the unconscious subject action, although revised and improved, the narratives written by the students had situations of their daily life that seemed to have been repressed. Consequently, on the Lacanian assumption that the unconscious is structured like a language, whose subject is born divided by the effect of language, this study aimed to analyze the incidence of unconscious subject in narrative texts written in the school environment. Therefore, the research was based on Interactionism of structuralist basis, reframed by Lacanian psychoanalysis, since the articulation between the structuralist linguistics and Lacanian psychoanalysis, in this theoretical proposal, allowed us to understand the subject captured by the linguistic-discursive functioning and the operation of significant order, and the points of departure and approach of the students productions in relation to the original texts. In that order, the analysis procedures have allowed to bring our work to the theoretical thought of Saussure, Jakobson, Lacan, Claudia Lemos, Sonia Borges, among others. Since this research analysis object consists in a collection composed of twenty-one fairy tales and wonderful tales individually written, it was necessary to define the corpus of analysis. Thus, we selected randomly four wonderful stories, which were written based on the tales Ali Baba and the Forty Thieves, John and the Beanstalk, Little Thumb and The Adventures of Pinocchio. The data showed that the authors of the narratives have transformed reality situations into significant, allowing the replacement of the original tales significant, more precisely scenarios, characters and scenes, sometimes showing a close relationship (identification) with the original text and sometimes being far from it, which possibly indicates the identification of the subject to another (imaginary), but also the subject's unconscious emergency, the subject's desire, throughout the language dimension.